MAPPING THE SCIENTIFIC LANDSCAPE OF PATIENT SAFETY WALKROUNDS: A BIBLIOMETRIC REVIEW - Ading Rohadi; Qurratul Aini (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
This study seeks to thoroughly map the scientific discourse on patient safety walkarounds by conducting an extensive bibliometric assessment. A Scopus search was performed for English-language publications containing the terms “patient safety” AND (“leadership walkround*” OR “walkarounds” OR “walk-around”). Thirty-three documents published between 2004 and 2024 were identified, averaging 1.65 publications per year, with the highest output in 2014. The United States produced the most literature, followed by the United Kingdom. The Joint Commission Journal on Quality & Patient Safety and BMJ Quality & Safety were the primary publication venues, and Frankel, A. emerged as the most productive author. Keyword mapping showed three dominant thematic clusters: (1) safety and leadership, (2) organizational culture, and (3) humans. Recent density patterns indicate rising attention to the first two themes. Publication trends demonstrate uneven and fluctuating growth. Patient safety culture is strongly linked to walkarounds, safety management, patient safety, organizational culture, and leadership.